2014
DOI: 10.1007/978-3-319-07788-8_29
|View full text |Cite
|
Sign up to set email alerts
|

Design and Evaluation of a Smart Library Using the APEX Framework

Abstract: User experience is a key point for successful ubiquitous computing (ubicomp) environments. The envisaged design should be explored as soon as possible to anticipate potential user problems, thus reducing redesign costs. The development of ubicomp environments' prototypes might help, providing feedback on the users' reaction to the environments. This paper describes the design and evaluation of ubicomp environments using APEX, a rapid prototyping framework providing user experience via a 3D application server a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…In order to compare the experience of using APEX-based prototypes at di↵erent levels of immersion, an exiting prototype of a smart library was used (see [1]). The user visible component of the prototype consists of a virtual world developed in OpenSimulator 4 (an open source multi-platform, multi-user 3D application server) and accessed through an appropriate viewer.…”
Section: A Smart Library Prototypementioning
confidence: 99%
See 1 more Smart Citation
“…In order to compare the experience of using APEX-based prototypes at di↵erent levels of immersion, an exiting prototype of a smart library was used (see [1]). The user visible component of the prototype consists of a virtual world developed in OpenSimulator 4 (an open source multi-platform, multi-user 3D application server) and accessed through an appropriate viewer.…”
Section: A Smart Library Prototypementioning
confidence: 99%
“…We have created the APEX framework [17], that relies on a three-dimensional (3D) application server to create simulations for ubiquitous environments. This framework was sucessfuly used in the prototyping of ubiquitous computing environments, enabling the detection of potential user problems (functional [16] or non-functional [1]) in the early phases of development, while reducing the cost of redesign.…”
Section: Introductionmentioning
confidence: 99%
“…Several ubicomp prototypes, mostly based on existing physical spaces, have been developed as part of the framework's design and development. Examples include a smart library [10,11] and an AAL system aimed at children who are asthma sufferers [6]. The present paper describes the first time the framework has been used to support a design exercise with real users.…”
Section: Apex Prototypingmentioning
confidence: 99%
“…Issues relating to type of engagement and how to collect data and feedback are important to understanding the value of this type of design. Previous experience, using the framework directly, has shown that engagement is easy to achieve [11,7]. This experience ranges from prototyping existing or envisaged ubicomp systems (e.g.…”
Section: Updated Requirementsmentioning
confidence: 99%
“…In recent years, with the rapid development of information networks and smart technologies, libraries have long ceased to be the only channel for readers to acquire knowledge resources. This marginalized crisis has prompted libraries to accelerate their entry into the social network process, proactively approaching users, and doing everything they can to make new innovations based on existing services [1][2][3][4]. Until the concept of "smart earth" was proposed by IBM in 2009, the wisdom library was widely concerned by domestic scholars.…”
Section: Introductionmentioning
confidence: 99%